Intelligent enterprise : - Quinn, James Brian (Free Press, 1992)
Quinn argues that the successful firms of the 1990s will be service oriented and will use innovative techonology to increase the range and improve the range of their services. Rapid response will be objective and flexibiltiy of management style will be the means. Quinn uses examples from companies such as Apple, Honda, ServiceMaster and Merck to show how a commitment to technological innovation married to a service-oriented outlook can produce impressive business results.